White matter correlates of scam susceptibility in community-dwelling older adults. - Lamar, Melissa; Arfanakis, Konstantinos; Yu, Lei; Zhang, Shengwei; Han, S. Duke; Fleischman, Debra A.; Bennett, David A.; Boyle, Patricia A. (Brain Imaging & Behavior, 2020)
Scam susceptibility places older adults - even those with intact cognition - at great risk. Lower grey matter volumes, particularly within right medial temporal regions, are associated with higher scam susceptibility; however, very little is known about white matter associates. We investigated associations between white matter integrity measured using diffusion tensor imaging (DTI) and scam susceptibility in 302 non-demented older adults (75% female; mean years: age = 81.3 + 7.5, education = 15.7 + 2.9). Participants completed comprehensive neuroimaging (including DTI, T1- and T2-weighted imaging), a self-report measure of scam susceptibility, and neuropsychological testing. Tract-Based Spatial Statistics (TBSS) investigated associations of DTI-derived measures of fractional anisotropy (FA), trace of the diffusion tensor, axial and radial diffusivity (separately) with scam susceptibility adjusting for age, sex, education, and white matter hyperintensities (WMH; total volume and voxelwise separately). Statistical significance was determined at p < 0.05, Family Wise Error corrected. TBSS revealed significant negative associations between FA in tracts connecting a number of right hemisphere white matter regions and scam susceptibility, particularly after additional adjustment for global cognitive functioning. The pathways implicated were mainly in right temporal-parietal and temporal-occipital regions. Association of trace, axial, and radial diffusivity with scam susceptibility were not significant in fully-adjusted models. Lower white matter integrity within right hemisphere tracts was associated with higher scam susceptibility independent of relevant confounds including global cognition. Thus, a right hemisphere brain network that includes key structures implicated in multi-sensory processing of immediate and future consequences may serve as a neurobiologic substrate of scam susceptibility in vulnerable older adults.